“Sorry, We're Closed” Bank Branch Closures, Loan Pricing, and Information Asymmetries - Bonfim, Diana; Nogueira, Gil; Ongena, Steven (Review of Finance, 2021)
Abstract We study local loan conditions when banks close branches. In places where branch closures do not take place, firms that purposely switch banks receive a sixty-three basis points (bps) discount. However, after the closure of nearby branches of their credit-granting banks, firms that locally and hurriedly transfer to other banks receive no such discount. Yet, the loan default rate for the latter (more expensive) transfer loans is on average a full percentage point lower than that for the former (cheaper) switching loans. This suggests that transfer firms are of “better” quality than switching firms. In sum, even if local markets remain competitive, when banks close branches, firms lose.